Analysis of factors influencing road performance of graphene-basalt fiber asphalt mixtures - ZHANG Yongqiang; YANG Wenjia; ZHANG Huzhu (矿业科学学报)
The graphene-basalt fiber asphalt mixtures(GBFAM) is a new composite modified material. In order to explore its road performance evolution characteristics and its influencing factors, on the basis of mixing ratio design, through wheel tracking, low-temperature bending beam, freeze-thaw splitting tests and the use of the response surface methodology, the influences of graphene content, basalt fiber content, and asphalt aggregate ratio on the dynamic stability, maximum bending strain, and freeze-thaw tensile strength ratio were analyzed, along with their significance levels. The results demonstrate that within a certain range of variation based on the optimum graphene content of 0.20 %, optimum basalt fiber content of 0.30 % and optimum asphalt aggregate ratio of 5.32 %, the dynamic stability, maximum bending strain, and freeze-thaw tensile strength ratio of the graphene-basalt fiber asphalt mixture tends to increase and then decrease with increasing graphene content, basalt fiber content, and asphalt aggregate ratio, reaching a maximum value near the optimum asphalt aggregate ratio, as well as the optimum graphene and basalt fiber contents. Among them, the asphalt aggregate ratio has a very significant influence on the dynamic stability, maximum bending strain, and freeze-thaw tensile strength ratio. The interaction between graphene and asphalt aggregate ratio has a significant influence on the maximum bending strain, and the effects of the remaining factors and their interactions are not significant.